The Correlation of Individual Factors with High Blood Pressure of Industrial Painters at a Land Transportation Manufacturing Company - Emmanuella Dyca Novayanti; Benny Dwi Prasetyo (JURNAL KESEHATAN LINGKUNGAN, 2021)
Introduction: The use of lead-based paint in the manufacturing process on land transportation production contributed to the decline of ambient air quality. The amount of lead level in the painting area exceeded the allowed Threshold Limit Value (TLVs). Excessive lead exposure will provoke the escalation of blood lead levels. Even in a small amount, a lead will cause cardiovascular disorder inside the human's body and raise blood pressure. The research aims to analyze the correlation between environmental factors and individual factors of industrial painters with high blood pressure. Methods: The research used a quantitative method and a cross-sectional design. It involved the whole industrial painters and administration workers at the Internal Control Division. Samples were taken from 20 workers determined using simple random sampling. Independent variables were air lead level, age, healthy family history of hypertension, nutritional status, caffeine consumption, and smoking frequency. Dependent variables were blood lead level and blood pressure. The data obtained from laboratory tests and questionnaires were analyzed using Fisher's Exact Test. Results and Discussion: Correlations were proven to exist between lead level in the work environment and lead level inside the painters' blood (p = 0.663). Family history of hypertension (p = 0.016) and nutritional status (p = 0.031) were correlated to the Blood Lead Levels (BLLs), whereas BLLs (p = 1.000), age (p = 0.158), caffeine consumption habit (p = 1.000), and smoking frequency (p= 0.663) were not correlated to the blood pressure. Conclusion: The work environment's lead level was correlated with BLLs but did no correlate with blood pressure. Family history of hypertension and nutritional status were the individual factors that correspond with high blood pressure in industrial painters.